2013
DOI: 10.4103/0976-500x.110882
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of multidrug resistance 1 expression and function in retinoblastoma cells by curcumin

Abstract: Objective:To determine the possible interaction of curcumin with P-glycoprotein (P-gp) expression and function by in vitro and in silico studies.Materials and Methods:In this study, curcumin was compared for its potential to modulate the expression and function of P-gp in Y79 RB cells by western blot, RT-PCR (reverse transcription polymerase chain reaction) and functional assay. Further, in silico molecular modeling and docking simulations were performed to deduce the inhibitory binding mode of curcumin.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Recently, several researchers also focused on the potential role of curcumin in Rb. Sreenivasan and his colleagues have reported that curcumin suppressed the expression of multidrug resistance associated protein 1 (MDR1) [ 29 ], thereby rendering Rb cells more sensitive to chemotherapy [ 30 ]. Another investigation demonstrated that curcumin induced the apoptosis of Y79 cells possibly through activating JNK and p38 MAPK pathways [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several researchers also focused on the potential role of curcumin in Rb. Sreenivasan and his colleagues have reported that curcumin suppressed the expression of multidrug resistance associated protein 1 (MDR1) [ 29 ], thereby rendering Rb cells more sensitive to chemotherapy [ 30 ]. Another investigation demonstrated that curcumin induced the apoptosis of Y79 cells possibly through activating JNK and p38 MAPK pathways [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…(30). Pgp activity can be modulated by a variety of non-substrate compounds which include physiological agents such as progesterone and curcumin (30, 31) and environmental toxins such as sterigmatocystin (32). In addition to altering Pgp activity, chemicals such as steroids and xenobiotics and several physiological/pathological conditions including chronic inflammation and oxidative stress could change its mRNA and protein levels (33).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of curcumin on P-gp expression, both at the mRNA and protein levels, are documented in many MDR tumor models [ 34 ], although its action on the pump function is more interesting. The action of curcumin on P-gp function, in fact, was demonstrated by studies on rhodamine 123 (Rh123) accumulation and efflux in different tumor models, as well as retinoblastoma, breast cancer, human cervical carcinoma, and chronic myeloid leukemia cell lines [ 35 , 92 , 93 , 94 ]. In particular, Sreenivasan et al [ 92 ] showed that curcumin-inhibited verapamil-stimulated ATPase activity of P-gp at higher concentrations and interacted at the substrate binding site of P-gp and not at the nucleotide-binding region.…”
Section: Curcuminmentioning
confidence: 99%
“…The action of curcumin on P-gp function, in fact, was demonstrated by studies on rhodamine 123 (Rh123) accumulation and efflux in different tumor models, as well as retinoblastoma, breast cancer, human cervical carcinoma, and chronic myeloid leukemia cell lines [ 35 , 92 , 93 , 94 ]. In particular, Sreenivasan et al [ 92 ] showed that curcumin-inhibited verapamil-stimulated ATPase activity of P-gp at higher concentrations and interacted at the substrate binding site of P-gp and not at the nucleotide-binding region. Analysis of the modulation of MDR by curcumin derivatives provided some evidence that confirms an inhibitory action on P-gp, both on its expression, mediated by three natural curcuminoids present in turmeric [ 95 ], and on its function, modulating P-gp mediated efflux through synthetic analogs of curcumin [ 35 , 96 , 97 , 98 ].…”
Section: Curcuminmentioning
confidence: 99%